Preliminary Web Accessibility Evaluation Method through the Identification of Critical Items with the Participation of Visually Impaired Users - Pereira, Letícia Seixas; Ferreira, Simone Bacellar Leal; Archambault, Dominique (Procedia computer science, 2015)
In order to ensure the access of the visually impaired to all information provided online it is necessary to remove existing barriers on the websites through several existent approaches, from recommendations to web development to validations of existing websites. The issues on navigating through the web that are detected only during the user's interactions on the sites, creates a need to evaluate this user's interactions aiming to ensure the web accessibility. So, in this scenery, this study uses previous researches on the subject and web accessibility rates in order to identify those barriers commonly founded by these users with total visual impairment, as well as to come up with a list of recommendations in order to optimize the evaluation process.